La política de distensión a partir de los años 80 y el resurgimiento de la sociedad civil en Argentina - Baisotti, Pablo (2006)
The return to democracy in Argentina, in the 1980’s was not an easily paved path at all. President Alfonsin had to manoeuvre among various actors like the armed forces, civil society, trade unions, political parties, and economic powers –domestic and international– that tried to reposition themselves in the new context. Thus, Argentina lived in the 80’s in a fragile balance that was often broken (military uprisings, hyperinflation) and that still remains to be solved. Approaching the Southern Cone countries, especially Brazil, gave credibility to the Radical administration; however, the precarious domestic situation weakened the government so much that it had to step down before completing its term of office.